EVALUATION OF THE PERFORMANCE OF WASTE MARBLE DUST AS A MINERAL FILLER IN HOT-MIX ASPHALT CONCRETE - Sang, Levy; Idowu, Temitope; Okumu, Victoria (Journal of Civil Engineering, Science and Technology, 2021)
As the construction industry continues to evolve globally, there is a need to develop best practices geared towards achieving sustainable construction. Asphalt concrete’s demand has been increasing steadily with an estimated global demand of 122.5 million tons in 2019. This is driven primarily by the growth in construction activities in developing countries as each country works towards enhancing its transportation facilities to cater to the ever-expanding population. Hence, there are needs to develop newer and more efficient means of asphalt consumption. One of such is identifying cheaper or waste materials for use in Asphalt production. This study, therefore, examined the viability of waste marble dust (WMD), an industrial waste produced during the shaping and polishing of marble blocks and also during its extraction from the mines, as a mineral filler in Hot-mix asphalt (HMA) concrete. Engineering properties such as Marshall stability and flow, Void characteristics, Indirect tensile strength and Tensile strength ratio properties were examined. It was observed that the addition of WMD steadily increased the Marshall Stability and indirect tensile strength values and lowered the voids percentages. The study’s major finding is that waste marble dust is highly suitable as a mineral filler in HMA and a 3% by volume addition of WMD in HMA at 4.5% binder content produced the most optimal mix for use in road pavements.